Penerapan Metode Agile Pada Sistem Informasi Perpustakaan Berbasis Website di SMA Amalul Khair Palembang - Fahlevi, Reza; Dhamayanti; Kesuma, Hendra Di (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
School libraries play a vital role in supporting the learning process, but library management at SMA Islam Al-Amalul Khair Palembang is still done manually, causing various operational constraints. This research aims to design and implement a website-based library information system using the Agile method to improve the efficiency of library management and services. The system development method used is Agile with stages including planning, design, implementation, testing, and evaluation. Data was collected through observation, interviews, and literature study. The result of this research is a library information system that provides features for searching book collections, digital book borrowing and returning, visitor attendance, fine management, and reporting that can be accessed by librarians, students, and school principals. This system is expected to improve the effectiveness of library services through process automation, structured data management, and provision of information that is easily accessible to all library users at SMA Islam Al-Amalul Khair Palembang.